Benchmarking global carrier status in the airline industry - Ellis, Darren; Leib, Steven (Purdue University Press, 2021)
Over the past decade or so and through the onset of the COVID-19 pandemic, a number of airlines have risen to global prominence in Asia (especially China), the Middle East, Latin America, Africa, and elsewhere. As each develops, many industry observers are questioning the extent to which these airlines will rival current industry heavyweights around the world. This paper aims to provide a basis for assessing what constitutes a major global carrier in the airline industry, including the likelihood of being so in the foreseeable future. Three key metrics are employed to gauge the global reach of an airline and its corresponding major global carrier status and rank: wide-bodied fleet size, the number of international destinations flown to, and continents served (squared for adequate amplification). Data are sourced from the Centre for Aviation (CAPA) airline database. The paper concludes that major global carrier status for an airline is best viewed in relation to key competitors including the ranking location of those directly above and below any given airline. This ranking approach is therefore about insights generated and is not premised on precise locations on a leader board.
Keywords: major global carrier; major airline; airline industry; global reach; benchmarking